The Imamiyyah Concept of “Sahabah” and the Attitude of Early Imamiyyah Commentators (I-IV/VI-X Centuries) to the Interpretation of the Sahabah - Habibov , Aslan (Scholarya Demo Journal of Ruby, 2023)
The sahabah (companions) have an important place in the history of interpretation. These individuals, who grew up with the Holy Prophet (pbuh) also witnessed the reasons for the revelation of the verses. In addition, the Qur'an has been revealed in Arabic and most of the Companions were Arabs. All these facts have made the Companions have a say in interpretation. For that very reason,  the interpretations of the Companions became one of the crucial sources for interpretations of the Ahl al-Sunnah narrations. The concept of "companions" of Ahl al-Sunnah also has a significant role in this matter. The attitude of the Imamiyyah commentators to the interpretation of the Companions is different from that of the Ahl al-Sunnah. Especially, the interpretation of narrations transmitted by the Companions are a minority in the early Imamiyyah tafsirs. Imamiyyah exegetes preferred Imams of Ahl al-Bayt instead of Companions in the matter of narrating the orders of the Holy Prophet (pbuh). Commentators have also highlighted the attitude of the Companions, whose opinions they conveyed, to the Ahl al-Bayt.The Shia interpretation that arose during the Tabi’in period (II/VIII centuries) passed through four stages. The early period, including the I-IV/VI-X centuries, is known as the stage of formation and development of Shia interpretation. The interpretations produced during that time were predominantly narrative in nature. Only a small number of early Shia interpretations have managed to survive until the present day. Studies show that early Imamiyyah commentators tended to overlook the interpretation of the Companions. Undoubtedly, their concept of "companion" has a role in this matter. According to Imamiyyah, in contrast to the Ahl al-Sunnah, not all companions are fair. In their opinion, the Companions are ordinary individuals, and some of them are fair and some of them are not.It can be said that the attitude of the early Imamiyyah commentators to the interpretation of the Companions the main role belongs to the notion of “imamate”. According to the Imamiyyah, the Imamate is a divine position that succeeds the Prophet (pbuh), wherein the appointment to this role is in the will of God and His Messenger, and it claims that the imams are infallible, possess ilmeladunni (God-given knowledge), and inherit the heritage of the Holy Prophet. As in other fields of Islamic science, the Imamiyyah considered the imams to be the main source of tafsir and kept the Companions in the background.